EVALUATION OF EGG.YOLK-GLYCEROL COMBINATION IN TRIS, CITRATE AND PHOSPHATE EXTENDERS FOR FREEZING OF RAM SEMEN - NEMA, S P; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Reproduction, 2011)
Three buffers, viz., tris fructose citric acid egg yolk glycerol (TFCEG), phosphate buffer with glucose fructosesodium citrate potassium chloride egg yolk glycerol- a synthetic phosphate medium (Phos) and sodium citrateglucose egg yolk glycerol (SCGEG) were tested for optimum egg yolk (6, 12, 20%) - glycerol (2, 4, 6%) combinationfor straw freezing of Patanwadi ram semen in a 3x3x3 factorial experiment. The motility of ram spennatozoa duringpre-freeze and post-thaw stages was preserved well with increasing levels of egg yolk in the medium, however,opposite was true for preservation of nonnal acrosome. Four per cent glycerol in all the three diluents could providesufficient protection to spenn motility. However, this level was little detrimental for maintaining the acrosomeintegrity. The interaction of egg yolk with glycerol revealed that 12 or 20% egg yolk incorporation with 4 % glycerollevel was good enough for tris and phos buffers, however, for citrate buffer 20 % egg yolk with 4 % glycerol level wasoptimum for freezing ram semen.
Keywords: Dilutors; Egg yolk; Glycerol; Freezability; Post-thaw recovery; Patanwadi ram; Semen